PENYELESAIAN SENGKETA KONSUMEN TIDAK BERJENJANG DI BADAN PENYELESAIAN SENGKETA KONSUMEN DITINJAU BERDASARKAN HUKUM PELINDUNGAN KONSUMEN - Suwandono, Agus; Harrieti, Nun; Darodjat, Rafan (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The consumer dispute resolution mechanism at the Consumer Dispute Settlement Agency is a non-tiered system for resolving consumer disputes. The purpose of this study is to determine and analyze the non-tiered consumer dispute resolution mechanism at the Consumer Dispute Settlement Agency, as well as its implications for consumer protection in consumer dispute resolution within the framework of consumer protection law. This research is a normative juridical study with descriptive analytical specifications. The results indicate that the non-tiered consumer dispute resolution mechanism at the Consumer Dispute Settlement Agency is based on an agreement between consumers and business actors. The non-tiered consumer dispute resolution mechanism at the Consumer Dispute Settlement Agency can cause uncertainty and a lack of legal protection for consumers in cases where no agreement can be reached on the form and amount of compensation in consumer dispute resolution through conciliation or mediation. Consumer dispute resolution through conciliation and mediation is highly dependent on consumer empowerment, awareness among business actors, and the good faith of the parties. Therefore, in order to provide opportunities for consumer dispute resolution at the Consumer Dispute Settlement Agency in stages, if the parties fail to reach an agreement, the dispute can be resolved through arbitration.